Optimization of single step multiplex PCR for detection of Eimeria tenella and Eimeria necatrix from commercial broilers - KHAN, MUHAMMAD UMAIR; ISLAM, SAHER; BAJWA, AMNA ARSHAD; RASHID, IMRAN; AKHTAR, RAHEELA; AKBAR, HAROON; SHEHZAD, WASIM; LATEEF, MUHAMMAD (The Indian Journal of Animal Sciences, 2016)
Multiplex polymerase chain reaction (PCR) was optimized for detection of 2 important species of Eimeria (Eimeria tenella and E. necatrix). This optimized protocol was used to screen 100 fecal samples collected from broiler birds in Lahore periphery. Out of 100 samples we found 6 tenella and only 1 E. necatrix positive by this method. The detection limit of oocysts by this method was as leastas 16 oocysts. This optimized multiplex PCR method can be used as routine diagnostic tool for detection of E. tenella and E. necatrix and can be extended up to the detection of 7 Eimeria species in future.